2019
DOI: 10.1371/journal.pone.0225149
|View full text |Cite
|
Sign up to set email alerts
|

“My mother in-law forced my husband to divorce me”: Experiences of women with infertility in Zamfara State of Nigeria

Abstract: IntroductionWomen with infertility have different experiences that determine the quality of their psychosocial health. Cultural constructions of infertility in Africa have made the experience of infertility among African women more burdensome. Yet, little is known about the psychosocial experiences of women with infertility in Zamfara State of Nigeria. The purpose of this study was to explore the psychosocial experiences of women with infertility in Zamfara.Materials and methodsAn exploratory qualitative desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 14 publications
4
28
1
Order By: Relevance
“…As the results of this study showed, there was a signi cantly negative correlation between stigma and FertiQoL. This is also supported by previous qualitative studies, where infertile women perceived that their daily lives were disrupted, and their marital relationship to have deteriorated, and complained that they had lower social status and social support during fertility treatment [35,36].…”
Section: Discussionsupporting
confidence: 87%
“…As the results of this study showed, there was a signi cantly negative correlation between stigma and FertiQoL. This is also supported by previous qualitative studies, where infertile women perceived that their daily lives were disrupted, and their marital relationship to have deteriorated, and complained that they had lower social status and social support during fertility treatment [35,36].…”
Section: Discussionsupporting
confidence: 87%
“…As the results of this study showed, there was a signi cantly negative correlation between stigma and FertiQoL. This is also supported by previous qualitative studies, where infertile women perceived that their daily lives were disrupted, their marital relationship to have deteriorated, and complained that they had lower social status and social support during fertility treatment [27,35].…”
Section: Discussionsupporting
confidence: 87%
“…Report of communication between girls and their husbands may suggest increased female reproductive agency, however, we do not know the nature of their reported communication and whether it is by choice. Spousal communication needs further scrutiny since couples’ decision-making concordance and quality of relationship have a direct bearing on contraceptive use [ 20 , 36 ], especially for married adolescent girls with limited agency in a gender unfriendly context. These reports of communication could have been due to in-laws’ pressure, conflicts with husbands, or pressure from husbands.…”
Section: Discussionmentioning
confidence: 99%